Estudos cinéticos e fotoquímicos de compostos de Ru(II) com ligantes bipiridínicos e bifosfínicos de fórmula geral cis- [RuCl2(P-P)(N-N)] (P-P = bifosfinas e N-N N-heterocíclicos bidentados) - Nascimento, Fábio Batista do (Universidade Federal de São Carlos, 2010)
In this thesis it were studied substitution reactions in ruthenium complexes of the type cis-[RuCl2(P-P)(N-N)] and cis-[RuCl2(dppb)(N-O)] (P-P = dppm, dppe, dppp and dppb; N-N = bipy, Me-bipy, MeO-bipy, Cl-bipy and fen; N-O = 2-acpy, 2-bzpy and 2- dpk). For all complexes, in a period of 24 hours, there was only the substitution of a chloride (Cl-) coordinated to the metal. The ligands used in substitution reactions and kinetic studies were: py, 4-pic and coordenant solvents (CH3CN and PhCN). Only the Cl- trans positioned to P of diphosphines was labilized giving rise to the entering ligand, confirming the greater trans effect of phosphine ligands in relation to N-N and N-O. The mechanism attributed to substitution reactions was dissociative because the reactions do not show dependence of ligand entry. DFT calculations showed the effective participation of the Cl atom trans to the P atom of the diphosphines in the formation of the HOMO orbital. This fact shows that the reactivity of Cl atoms is different and they can be replaced selectively. Good linearity was observed for the percentage of participation of d orbitals of ruthenium in the formation of HOMO for the dissociation of Cl- complex indicating that the strength of the Ru-Cl- bond is due to the direct interaction of the orbitals of Cl- and the d orbitals of ruthenium. Exploratory studies using irradiation of light at fixed wavelengths were performed to study possible influence of the effect of the exchange rate of Cl- and also on the isomerization reaction trans/cis-[RuCl2(dppb)(bipy)]. An increase in the rate of exchange reaction was observed in the kinetics of substitution. In the isomerization processes were not observed. The substitution reactions of Cl- in the complexes cis- [RuCl2(dppb)(N-N)] (N-N = bipy and phen) by nitrile ligands (e.g. PhCN and CH3CN), lead to the formation of complexes in which trans ligands L were coordinated by the nitrogen atom of the ligands N-N in the final complex. However, studies of 31P{1H} NMR and cyclic voltammetry confirmed that the reactions take place initially with the replacement of L trans to P atom followed by an isomerization process. This is attributed to the strong competition of π between nitrile and phosphine ligands, and its final position is determined by this effect.
Kinetics ans Photochemical studies of Ru(II) compounds with Diimine and Diphosphine ligands of general formulae cis-[RuCl2(PP)(N-N)] (P-P = Diphosphines and N-N Bidentades N-Heterociclic ligands)
Keywords: Química inorgânica; Complexos de rutênio; Cinética; Reações de substituição; Reatividade (Química); CIENCIAS EXATAS E DA TERRA::QUIMICA